KONTRIBUSI WISATA D’MOOAT TERHADAP PENDAPATAN KELUARGA SEKITAR DESA MOOAT KABUPATEN BOLAANG MONGONDOW TIMUR - Munawir Kohongia; Agnes E. Loho; Rine Kaunang (Jurusan Sosial Ekonomi Pertanian, Fakultas Pertanian Universitas Sam Ratulangi, Manado, 2019)
This study aims to determine D’Mooat's tourism contribution to the Family Income around Moat Village, East Bolaang Mongondow Regency. The research was conducted from July to September 2018. The research method used in this study was the Case Study method. The data used were primary data and secondary data. Primary data were obtained through a list of questioner that had been prepared, while secondary data were obtained from the sub-district office, the village office, and related agencies. The analysis used was descriptive analysis. The results showed that community income from tourism activities of D'Mooat had a high contribution to family income, which was as high as 45.3%.Keywords: Family Income, Responden Incomen, D’Mooat, tourism activities, contribution